Integrative taxonomy reveals two new species of karst-dwelling Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from the border region of Laos and Vietnam - Luu, Vinh Quang; Hoang, Tuoi Thi; Ha, Hong Bich; Grismer, Jesse L.; Murdoch, Matthew; Sitthivong, Saly; Phimpasone, Vilay; Grismer, L. Lee (Zootaxa, 2024)
An integrative taxonomic analysis of the gekkonid lizard genus Hemiphyllodactylus was conducted using molecular, morphological, color pattern, and ecological data on a clade of 19 species, including two new species from karst landscapes in northern Laos and Vietnam. Hemiphyllodactylus houaphanensis sp. nov. (Laos) and H. vanhoensis sp. nov. (Vietnam) are karst-dwelling species whose discovery further emphasizes the unrealized herpetological diversity and site-specific endemism in karst ecosystems across Southeast Asia and the need for increased field work to protect these biodiverse landscapes.